Extremism and the psychology of uncertainty - Hogg, Michael A., 1954-; Blaylock, Danielle L. (Malden, MA : Wiley-Blackwell, 2012)
Extremism and the Psychology of Uncertainty showcases cutting-edge scientific research on the extent to which uncertainty may lead to extremism. Contributions come from leading international scholars who focus on a wide variety of forms, facets and manifestations of extremist behavior.@* Systematically integrates and explores the growing diversity of social psychological perspectives on the uncertainty--extremism relationship@* Showcases contemporary cutting edge scientific research from leading international scholars @* Offers a broad perspective on extremism and focuses on a wide variety of different forms, facets and manifestations@* Accessible to social and behavioral scientists, policy makers and those with a genuine interest in understanding the psychology of extremism.
Front Matter -- Theories and Concepts. The Need for Certainty as a Psychological Nexus for Individuals and Society / Arie W Kruglanski, Edward Orehek -- Self-Uncertainty, Social Identity, and the Solace of Extremism / Michael A Hogg -- Extremism is Normal / Dominic Abrams -- The Psychology of the Absurd / Travis Proulx -- Radical Worldview Defense in Reaction to Personal Uncertainty / Kees van den Bos, Annemarie Loseman -- The Uncertainty-Threat Model of Political Conservatism / John T Jost, Jaime L Napier -- Individuals and Groups. Dying to be Popular / Jason T Siegel, William D Crano, Eusebio M Alvaro, Andrew Lac, David Rast, Vanessa Kettering -- The Extremism of Everyday Life / Mark J Landau, Zachary K Rothschild, Daniel Sullivan -- Religious Zeal after Goal Frustration / Ian McGregor, Kyle A Nash, Mike Prentice -- Dehumanization, Demonization, and Morality Shifting / Roger Giner-Sorolla, Bernhard Leidner, Emanuele Castano -- Light from Dark / Todd L Pittinsky -- Groups and Society. Uncertainty, Insecurity, and Ideological Defense of the / Christopher M Federico, Grace M Deason -- Authoritarianism, Need for Closure, and Conditions of Threat / Jennifer L Merolla, Jennifer M Ramos, Elizabeth J Zechmeister -- Constructing Extremism / Viviane Seyranian -- Collective Uncertainty and Extremism / Fathali M Moghaddam, Karen Love -- Uncertainty, and the Roots and Prevention of Genocide and Terrorism / Ervin Staub -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Fanaticism -- Psychological aspects; Radicalism -- Psychological aspects; Uncertainty -- Psychological aspects; Extremists -- Psychology; PSYCHOLOGY -- Mental Health; Electronic books; Electronic books